Emerging Issues in People Management Governance in Public Administration:: an integrative literature review (Management and Connections Journal, 2024)
This study aimed to explore the main issues and trends related to people management governance in public administration, with a particular focus on staff training and motivation. To this end, we conducted an Integrative Systematic Review (ISR) of articles published between September 2012 and December 2022. We used rigorous eligibility criteria to select eighteen relevant articles from the ISI Web of Science (Thomson Reuters Scientific), Scopus (Elsevier), and Capes Journals databases. The results indicate that people management is seen as a key factor for organizational performance and quality of public services, being a tool to increase the efficiency and effectiveness of the public sector. However, the study also revealed challenges and gaps, including the need for more effective management of diversity and inclusion, and the coordination and responsibility of public servants.
Keywords: Governance; People Management; Public Administration; Organizational Performance; Public Services